Brain Stimulation in Obsessive-Compulsive Disorder (OCD): A Systematic Review - Rapinesi, Chiara (Curr Neuropharmacol, 2019)
BACKGROUND: Obsessive-compulsive disorder (OCD) is a highly prevalent, severe, and chronic disease. There is a need for alternative strategies for treatment-resistant OCD. OBJECTIVE: This review aims to assess the effect of brain stimulation techniques in OCD. METHOD: We included papers published in peer-reviewed journals dealing with brain stimulation techniques in OCD. We conducted treatment-specific searches for OCD (Technique AND ((randomized OR randomised) AND control* AND trial) AND (magnetic AND stimulation OR (rTMS OR dTMS)) AND (obsess* OR compuls* OR OCD)) on six databases, i.e., PubMed, Cochrane, Scopus, CINAHL, PsycINFO, and Web of Science to identify randomised controlled trials and ClinicalTrials.gov for possible additional results. RESULTS: Different add-on stimulation techniques could be effective for severely ill OCD patients unresponsive to drugs and/or behavioural therapy. Most evidence regarded deep brain stimulation (DBS) and transcranial magnetic stimulation (TMS), while there is less evidence regarding transcranial direct current stimulation (tDCS), electroconvulsive therapy, and vagus nerve stimulation (for these last two there are no sham-controlled studies). Low-frequency TMS may be more effective over the supplementary motor area or the orbitofrontal cortex. DBS showed best results when targeting the crossroad between the nucleus accumbens and the ventral capsule or the subthalamic nucleus. Cathodal tDCS may be better than anodal in treating OCD. Limitations. We had to include methodologically inconsistent underpowered studies. CONCLUSION: Different brain stimulation techniques are promising as an add-on treatment of refractory OCD, although studies frequently reported inconsistent results. TMS, DBS, and tDCS could possibly find some use with adequate testing, but their standard methodology still needs to be established.